Evaluation of mechanical and physicochemical properties of protection coatings obtained by sol-gel method - Tkaczyk, M.; Krzak-Ros, J.; Kaleta, J. (Фізико-хімічна механіка матеріалів, 2012)
Thin coatings, obtained by the sol-gel method, could find potential applications in medical, chemical and food industry. To achieve this, coatings need to have proper physicochemical, mechanical and protective properties. Titanium dioxide (TiO₂) and silicon dioxide (SiO₂) coatings have been applied onto the surface of a stainless steel (316L) by the solgel method using two techniques: dip-coating and painting. To determine the physicochemical composition of triple SiO₂ and TiO₂ coatings, samples were examined by Raman spectroscopy. Surface images obtained with the use of a scanning electron microscopy allow us to determine the surface morphology and continuity of the coatings. The surface morphology was examined before and after tensile tests. The static tensile tests and fatigue strength tests were conducted on a hydraulic testing machine MTS 810 with a measuring range of up to 100 kN. A preliminary research has confirmed that the coatings obtained by the sol-gel method have physicochemical, mechanical and protective properties that make it possible to use them as protective coatings. Тонкі покриви на основі SiO₂ та TiO₂, отримані золь-гель методом, застосовують у медицині, хімічній та харчовій промисловості. Для досягнення необхідних їх фізико-хімічних, механічних і захисних властивостей використано оптимальні режими золь-гель методу, щоб одержати покриви на основі диоксидів титану та кремнію на поверхні нержавної сталі типу 316L. Для оцінки властивостей покривів вжито методи раманівської спектроскопії, а поверхню досліджено за допомогою сканівного електронного мікроскопа. Морфологію поверхні вивчали до та після випробувань на розтяг на гідравлічній машині MTS 810 з навантаженнями до 100 kN. Встановлено, що покриви володіють необхідними фізико-хімічними та механічними властивостями, щоб їх застосовувати як захисні. Тонкие покрытия на основе SiO₂ и TiO₂, полученные золь-гель методом, применяют в медицине, химической и пищевой промышленности. Для достижения необходимых их физико-химических, механических и защитных свойств применены оптимальные режимы золь-гель метода для формирования покрытий на основе диоксидов титана и кремния на поверхности нержавеющей стали типа 316L. Для оценки свойств покрытий использованы методы рамановской спектроскопии, а поверхность исследована с помощью сканирующего электронного микроскопа. Морфологию поверхности изучали до и после испытаний на растяжение на гидравлической машине MTS 810 с нагрузками до 100 kN. Выявлено, что покрытия владеют необходимыми физико-химическими и механическими свойствами, чтобы их применять в качестве защитных.